RhoB Differentially Controls Akt Function in Tumor Cells and Stromal Endothelial Cells during Breast Tumorigenesis - Kazerounian, Shiva (2012)
Tumors are composed of cancer cells but also a larger number of diverse stromal cells in the tumor microenvironment. Stromal cells provide essential supports to tumor pathophysiology but the distinct characteristics of their signaling networks are not usually considered in developing drugs to target tumors. This oversight potentially confounds proof-of-concept studies and increases drug development risks. Here, we show in established murine and human models of breast cancer how differential regulation of Akt by the small GTPase RhoB in cancer cells or stromal endothelial cells determines their dormancy versus outgrowth when angiogenesis becomes critical. In cancer cells in vitro or in vivo, RhoB functions as a tumor suppressor that restricts EGF receptor (EGFR) cell surface occupancy as well as Akt signaling. However, after activation of the angiogenic switch, RhoB functions as a tumor promoter by sustaining endothelial Akt signaling, growth, and survival of stromal endothelial cells that mediate tumor neoangiogenesis. Altogether, the positive impact of RhoB on angiogenesis and progression supercedes its negative impact in cancer cells themselves. Our findings elucidate the dominant positive role of RhoB in cancer. More generally, they illustrate how differential gene function effects on signaling pathways in the tumor stromal component can complicate the challenge of developing therapeutics to target cancer pathophysiology.